Hazard Analysis for Safety-critical Systems Using SOFL - Azma, Abdullah; Liu, Shaoying (2013)
The most important mechanism for improving the safety of a system is to identify the hazard state of the system as it has the potential to cause an unexpected, unplanned or undesired event or a series of events. A hazard that occurs in a system could inevitably lead to an accident (loss event), which could result in an injury or illness or even loss of a human life, and the hazard could also have a negative impact on the environment. An approach in hazard analysis is proposed in this paper in order to avoid hazard from happening in a safety-critical system. The approach consists of three steps: (1) deriving hazards from safety properties, (2) using Fault Tree Analysis (FTA) to analyze the possible causes of each hazard, and (3) converting each minimal cut-set of FTA into a formal property in terms of variables used in the formal specification. A case study based on an Auto-cruise Control (ACC) system for vehicles is used as an example to illustrate the process.